Automation and ‘Thailand +1” Strategy of Japanese Companies in Thailand by Thai Engineers - Mayasuki Kondo (Center for Science and Technology Development Studies, Indonesian Institute of Sciences, 2021)
AbstractJapanese companies have the second largest number of overseas manufacturing sites in Thailand after in China. To cope with labor cost increase, on one hand, they automate their production processes using robots. On the other hand, they establish satellite manufacturing sites in neighboring lower labor cost countries. This movement is called “Thailand+1” Strategy. The paper discusses these two movements comparing with the experiences of Japanese companies in Japan in the late 1980s coping with rapid Japanese Yen appreciation. The paper discusses that the automation in Thailand now is more systematic and needs system integrators and that local engineers need to be trained as system integrators since the technological operation in Thailand is already heavily localized. In the case of Japan in the late 1980s, shop-floor workers were needed to be mechatronics operators since individual machines became IT (Information Technology) -based. For the “Thailand +1” Strategy, only a part of production process, which is heavily labor-intensive, is moved out as a satellite factory, while in the case of Japan in the 1980s a whole assembling process was moved out and many parts suppliers followed. Another difference is that local engineers (Thai engineers) play an important role in technology transfer in the case of the “Thailand +1” Strategy, while Japanese engineers transferred technology to overseas factories in the case of Japanese companies in the late 1980s. Japanese companies have become globally operated from Japan-centered. Keywords: Automation, Thailand+1 Strategy, Japanese Companies, Thai Engineers